Strategi Guru dalam Mengintegrasikan Teknologi Informasi dan Komunikasi (ICT) dengan Sumber Belajar Pendidikan Agama Islam di Madrasah Aliyah NW Sekunyit - Abid Rahman Asrowi; Irwan Gunandi; Akhmad Syahri; Mustain (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze teachers' strategies in integrating Information and Communication Technology (ICT) with Islamic Religious Education (PAI) learning resources at Madrasah Aliyah NW Sekunyit. The research employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation involving the school principal, PAI teachers, and other relevant stakeholders. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that teachers implement various strategies to integrate ICT with PAI learning resources, including the use of digital presentation media, Islamic educational videos, internet-based learning resources, and the combination of conventional learning materials with digital media in the teaching and learning process. However, the implementation of these strategies faces several challenges, such as limited technological facilities and infrastructure, insufficient digital competencies among some teachers, age-related factors, limited ICT training opportunities, and inadequate internet access. To address these challenges, teachers adopt various adaptive measures, including collaboration between senior and younger teachers, shared use of available facilities, participation in online self-directed training, and the optimization of existing technological resources within the school. The study concludes that the successful integration of ICT with PAI learning resources depends not only on the availability of technological facilities but also on teachers’ creativity, adaptability, and commitment to developing learning practices that meet the demands of the digital era